Hubungan Kinerja dan Kepribadian Guru Kimia dengan Minat Belajar Peserta Didik - Agustina, Wahyuni; Aulia, Army; Hasri, Hasri (Program Pasca Sarjana UNM, 2020)
The study aims at discovering the correlation between performance and personality of Chemistry teacher towards students’ learning interest at SMAN 9 Makassar based on students’ opinions. The type of this study is ex-post facto. Sample collection technique employed purposive sampling. The sample of the study consisted of 118 students from class X, XI, and XII at SMAN 9 Makassar. Data collection employed a questionnaire with Likert scale with five alternative answers, which consisted of a positive statement with the scoring of 5,4,3,2,1 and a negative statement with the scoring of 1,2,3,4,5. Data analysis of the study employed statistics descriptive analysis and inferential analysis with correlation and regression techniques. The results of the study reveal that (1) there is a correlation between the performance of Chemistry teacher on students’ learning interest at SMAN 9 Makassar with low category, (2) there is a correlation between the personality of Chemistry teacher on students’ learning interest at SMAN 9 Makassar with low category, and (3) there is a correlation between the performance and personality of Chemistry teacher towards students’ learning interest at SMAN 9 Makassar with low category. Then the conclusion is, there is a correlation between performance and personality of chemistry teacher toward students learning interest at SMA 9 Makassar.